Losing the stem-loop structure from metazoan mitochondrial tRNAs and co-evolution of interacting factors - Watanabe, Yoh-ichi; Suematsu, Takuma; Ohtsuki, Takashi (Frontiers in Genetics, 2014)
Conventional tRNAs have highly conserved sequences, four-armed cloverleaf secondary structures, and L-shaped tertiary structures. However, metazoan mitochondrial tRNAs contain several exceptional structures. Almost all tRNAsSer for AGY/N codons lack the D-arm. Furthermore, in some nematodes, no four-armed cloverleaf-type tRNAs are present: two tRNAsSer without the D-arm and 20 tRNAs without the T-arm are found. Previously, we showed that in nematode mitochondria, an extra elongation factor Tu (EF-Tu) has evolved to support interaction with tRNAs lacking the T-arm, which interact with C-terminal domain 3 in conventional EF-Tu. Recent mitochondrial genome analyses have suggested that in metazoan lineages other than nematodes, tRNAs without the T-arm are present. Furthermore, even more simplified tRNAs are predicted in some lineages. In this review, we discuss mitochondrial tRNAs with divergent structures, as well as protein factors, including EF-Tu, that support the function of truncated metazoan mitochondrial tRNAs.